2021
DOI: 10.3389/fphar.2021.607403
|View full text |Cite
|
Sign up to set email alerts
|

Ficus erecta Thunb. Leaves Ameliorate Cognitive Deficit and Neuronal Damage in a Mouse Model of Amyloid-β-Induced Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) pathogenesis is linked to amyloid plaque accumulation, neuronal loss, and brain inflammation. Ficus erecta Thunb. is a food and medicinal plant used to treat inflammatory diseases. Here, we investigated the neuroprotective effects of F. erecta Thunb. against cognitive deficit and neuronal damage in a mouse model of amyloid-β (Aβ)-induced AD. First, we confirmed the inhibitory effects of ethanol extracts of F. erecta (EEFE) leaves on Aβ aggregation in vivo and in vitro. Next, behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…At present, plant therapy for AD has attracted more and more attention because of its comprehensive effects and less side effects ( Mithu et al, 2014 ; Sun et al, 2014 ; Yan et al, 2017 ; Martínez-Coria et al, 2019 ; Singh et al, 2019 ; Baranowska-Wójcik et al, 2020 ; Hosseini et al, 2021 ; Nowak et al, 2021 ; Sohn et al, 2021 ; Anupama et al, 2022 ). The mystery fruit, which we used in this study, has also received more attention due to its good antioxidant properties, including lowering cholesterol ( Huang et al, 2020 ), antidiabetic effects ( Obafemi, et al, 2019 ), reducing serum uric acid levels ( Shi et al, 2016 ), and anti-oxidative damage ( Chen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, plant therapy for AD has attracted more and more attention because of its comprehensive effects and less side effects ( Mithu et al, 2014 ; Sun et al, 2014 ; Yan et al, 2017 ; Martínez-Coria et al, 2019 ; Singh et al, 2019 ; Baranowska-Wójcik et al, 2020 ; Hosseini et al, 2021 ; Nowak et al, 2021 ; Sohn et al, 2021 ; Anupama et al, 2022 ). The mystery fruit, which we used in this study, has also received more attention due to its good antioxidant properties, including lowering cholesterol ( Huang et al, 2020 ), antidiabetic effects ( Obafemi, et al, 2019 ), reducing serum uric acid levels ( Shi et al, 2016 ), and anti-oxidative damage ( Chen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, because of the clinical trial failures and multiple sides of synthetic drugs, the development of phytotherapy has received close attention from the public and the scientific community ( Vegh, et al, 2019 ). Many foods and nutritional drugs are claimed to have memory-improving effects, including Ginkgo biloba ( Singh, et al, 2019 ; Nowak, et al, 2021 ), dihydromyricetin ( Martínez-Coria, et al, 2019 ), linalool ( Hosseini et al, 2021 ), fig leaves ( Sohn et al, 2021 ), Schisandra polysaccharides ( Sun et al, 2014 ), Nardostachys jatamansi ( Anupama et al, 2022 ), tea ( Baranowska-Wójcik, et al, 2020 ), Forsythia ( Yan et al, 2017 ), curcumin ( Mithu et al, 2014 ), and acidic polysaccharose ( Mithu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these markers have demonstrated that variations in nucleotide sequences can provide a rapid method for the molecular identification of F. erecta. Our focus on F. erecta is due to its medicinal effects, as discussed in recent studies [5,6]. Despite the limited and geographically confined number of samples, we designed primers that incorporate the published plastome sequences of Japanese F. erecta (GenBank accession No.…”
Section: Implications Of Mdcs Data and Molecular Markers For Ficus Er...mentioning
confidence: 99%
“…King, which has narrower lanceolate leaves, though the exact distinction between the two remains unresolved. Recent research has highlighted several beneficial properties of extracts from this species, including tyrosinase inhibition, thrombolytic action, antioxidant properties, cytotoxic effects, and neuroprotective capabilities [3][4][5][6]. In Korea, two more varieties, F. sarmentosa var.…”
Section: Introductionmentioning
confidence: 99%